PENGARUH KENAIKAN HARGA BAHAN BAKAR MINYAK TERHADAP INDEKS HARGA SAHAM GABUNGAN DI BURSA EFEK INDONESIA - Rio Andriawan; Utik Bidayati (Jurnal Fokus Manajemen Bisnis, 2014)
This study entitled â€œThe Effect of Fuel Price Increase Against Composite Stock Price Index In Indonesia Stock Exchangeâ€, with populations used in this study is a data sample JCI JCI to 8 working days before and 8 days of work after the fuel price hike june 22 2013, researchers assume that the time span of the study will occur the impact of rising fuel prices which impact on the presence of differences in returns and significant abnormal return 8 working days 8 working days before and after the increase in fuel prices, this is evidenced by the value of Î± <sig. Ie 0.05 <0.064. While the subsequent twsting using a one sample t-test to get the result there is no significant abnormal return in 8 working days before and 8 days after the work is evidenced by the increase in fuel prices Î± < sig. Significance before and after values for 0.689 and 0.605. In this study it can be concluded that in th present impact of an event does not occur at yhe time of approaching the event.